Effectiveness of Manipulative Media in Improving Learning Outcomes of Fraction Addition in Elementary School - Rukono, Rukono; Raharjo, Tri Joko; Pramono, Suwito Eko (International Journal of Education, Information Technology, and Others, 2025)
Learning done by teachers is still conventional and minimal in the use of concrete learning media. So this study aims to examine the effectiveness of using manipulative media in improving math learning outcomes, especially in the material of adding fractions with different denominators in elementary schools. The method used is library research with a descriptive qualitative approach. Data were obtained through a literature search on Google Scholar, with the criteria of relevant articles, accessible in fulltext, and published in the last six years (2018-2024). Of the 20 articles found, 6 of them were analyzed further because they had a direct relationship with the research topic. The results of the analysis showed that the use of manipulative media, whether in the form of paper, blocks, or transparent mica, proved effective in improving students' concept understanding and learning outcomes. This finding is reinforced by the significant increase in students' learning evaluation scores in various studies. Therefore, manipulative media is recommended as an alternative for interactive and meaningful learning in teaching mathematics at the primary school level.